The Methods of Calculating Zakat in Islamic Economicy (Calculating the Zakat of agricultural wealth) - Abdullah Muhammad Qader Gubriel (Zanco Journal of Humanity Sciences)
In the name of Allah، Most Gracious، Most Merciful Zakat is the third of the five main pillars of the true Islamic religion، which includes: The pronouncement of the Shahada، the establishment of the prayer، the payment of alms Zakat، the fasting of Ramadan and Pilgrimage to the home- Kaaba - if he is able to go.